I.ii. Task Force on Politics, Strategy and Organisation, - Democratic Left (Political Party: Ireland) (1993)
This series contains the records of the Democratic Left task force on politics, strategy and organisation. It includes: notice of meetings; submissions from individual members and units of the organisation; minutes of the 'sub-committee on party organisation'; discussion documents; interim reports; final task force report entitled 'Strategy 2000: A radical agenda for change', dated October 1993; and 'Towards 2001: Draft report of the Democratic Left task force on politics, strategy and organisation', dated April 1993.